Fatigue performance of asphalt with different conventional binders - Lim, R.; Chegenizadeh, Amin; Nikraz, Hamid (Australian Geomechanics Society, 2016)
A series of experiments has been conducted at Curtin University, Australia to explore the influence of different conventional binders used in asphalt mixes on their fatigue performance. Fatigue cracking is one of the key distress modes occurring in flexible pavements. The different binders used in this research differs in viscosity. Through this study, results showed that the flexural stiffness decreases as the repetitive load cycles are applied. Results in this study also show that the fatigue life varies with the increase of viscosity of binders used in the asphalt mix. The fatigue life found in this study decreases from Class 320 asphalt mix to Class 170 and then Class 600. In addition the tests were carried out in a constant temperature, strain level and loading frequency. In this research, the fatigue life of asphalt mixtures with different conventional binders was evaluated through a four point bending test in strain controlled mode and with harvasine loading. The fatigue life of the asphalt mixtures has been assessed and determined based on the 50% reduction in the initial flexural stiffness.